A Conjunction of Grammatical Cohesion in BBC News About Taylor Swift is Time’s 2023 Person of The Year - Nadifa, Tri; Alam, Beny; Hadi, Imron (Sekolah Tinggi Bahasa Asing JIA, 2024)
This study examines how conjunctions are used in BBC news articles, with a particular focus on the article titled “Taylor Swift is TIME’s 2023 Person of the Year”. By identifying different types of conjunctions, this study categorizes them into external and internal types and analyses their role in ensuring sentence coherence. Conducted over six months at STBA JIA, this study adopts a descriptive qualitative method and is based on Halliday and Hasan (1976) theory of grammatical cohesion. The findings indicate that simple additive conjunctions are the most frequent, accounting for 33.33% of all instances. Temporal conjunctions follow, with 29.16% for simple types and 8.4% for complex types. Among the classifications, external conjunctions dominate at 87.5%, reflecting the emphasis on real-world connections and events presented in the news.